(untitled) (Research Journal on Multi-disciplinary Issues, 2026)
Nepal’s freshwater fisheries are critically dependent on monsoon driven hydrological cycles. This review explores the impacts of reduced rainfall on fisheries and aquaculture in Madhesh Province, with a focus on understanding the decreased precipitation on fish reproduction, migration patterns, and habitat condition and socio-economic consequences for local fishing communities due to climate change. Madhesh Province, characterized by its warm climate and fertile lowlands, is a key region for freshwater aquaculture, particularly of species such as carp and tilapia. However, declining and erratic rainfall has led to reduced water availability in ponds, rivers, and wetlands, significantly affecting fish growth, breeding cycles, and overall productivity. These climate changes occurs due to rising temperatures and increased evaporation stress on aquatic ecosystems and raise the risk of disease outbreaks, with significant socio economic impacts on fishing communities who rely heavily on seasonal water availability for their livelihoods. In Madhesh Province, where aquaculture supports food security and income, reduced rainfall exacerbates poverty, reduces employment, and increases vulnerability. This review underscores the urgent need for adaptive management strategies, including improved water resource governance, climate resilient aquaculture practices, and livelihood diversification, to mitigate the impacts of climate variability on fisheries and enhance resilience in the region.